Unusual acid- and base-catalyzed C-N bond formation approach through reaction of chromonyl Meldrum’s acid and nitrogen binucleophiles - Balalaie, Saeed; Bijanzadeh, Hamid Reza; Mehrparvar, Saber; Rominger, Frank (Synlett, 2016)
Reaction of chromonyl Meldrum’s acid and N-substituted 2-aminobenzamides was studied in the presence of acidic and basic catalysts. The use of methanesulfonic acid as a catalyst in this reaction led to the synthesis of chromonyl quinazolinones through employing Meldrum’s acid as a carbon leaving group. However, in the presence of basic catalyst, this reaction gave functionalized 2-pyridones.
Published online: 30.11.2015
Gesehen am 19.08.2020